Peningkatan Literasi Energi Terbarukan melalui Sosialisasi Pembangkit Listrik Tenaga Surya di PT. PLN Nusantara Power - Moh. Syaiful Anwar; Mochamad Shaleh; Bambang Triono (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The transition toward renewable energy requires not only technological development but also improvement in human resource literacy, particularly in understanding solar power systems. This community service activity aimed to enhance renewable energy literacy through socialization of Solar Power Plant (Pembangkit Listrik Tenaga Surya/PLTS) at PT. PLN Nusantara Power. The program was conducted on 8–9 October 2024 and involved 15 employees as participants. The implementation method consisted of three main stages: preparation, socialization, and evaluation. The socialization stage was carried out over two sessions, focusing on basic concepts of solar energy and technical aspects of PLTS, including system components and grid integration. Knowledge improvement was measured using pre-test and post-test instruments based on key literacy indicators. The results showed a consistent increase in participants’ understanding across all indicators, indicating the effectiveness of the structured and interactive learning approach. The discussion-based method also encouraged active participation and contextual understanding related to workplace applications. Overall, the program successfully improved participants’ renewable energy literacy and strengthened their awareness of solar energy utilization in power generation systems.